Use of Panicker’s cannula in management of atonic postpartum hemorrhage - Rana, Vaidehi; Patel, Alpesh; Patel, Vipul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Postpartum hemorrhage (PPH) is leading cause of maternal mortality worldwide. Panicker’s cannula creates negative pressure inside the uterus that causes shrinking of the uterus which can assist the physiological process of contraction and retraction to stop atonic postpartum hemorrhage. It is safe and simple technique to prevent and treat PPH. It can be used in low-resource and primary care settings, where even para medical personnel can use this method effectively to prevent morbidity and mortality. This can also be used in non-PPH conditions. In this study total 20 women with singleton pregnancy (14 had vaginal delivery and 6 underwent cesarean section), who developed atonic postpartum hemorrhage were included in the study. Panicker’s cannula was used in the patients, in whom bleeding was not stopped despite using uterotonics. Cessation of complete bleeding was observed in all 20 women within 4 minutes, which was associated with contraction and firm retraction of the uterus. Amount of the blood in bottle ranged from 150-250 ml. Vacuum retraction of uterus assists in the normal physiological process of contraction and retraction. This simple and cost effective technique, takes very little time to stop bleeding. This lifesaving technique is useful in all settings especially in low resource settings.